Penerapan Model Pembelajaran Contextual Teaching and Learning Dalam Meningkatkan Hasil Belajar pada Siswa Kelas VIII Mata Pelajaran Fiqih di MTs Teladan Gebang - Maulida Maulida; Wadhuli Jannati (LPPM Institut Nasional Laa Roiba Bogor, 2020)
The purpose of this study is to find out how the application of the Contextual Teaching and Learning learning model for class VIII students in FIQIH subjects at MTs. Exemplary Gebang. To find out how to improve student learning outcomes for class VIII FIQIH subjects at MTs. Exemplary Gebang. To find out whether the application of the Contextual Teaching and Learning learning model can improve the learning outcomes of class VIII students in FIQIH subjects at MTs Teladan Gebang. Learning outcomes are something that cannot be separated from learning. Based on the observation activities that have been carried out, the background of this research is that students are less active in the learning process, students are less confident in expressing opinions, students are more focused on their own activities when listening to the explanation given by the teacher, so this has an impact on student learning outcomes in Fiqh lessons is still low, in class VIII students, totaling 32 students at MTs Teladan Gebang, it is known that the learning process is less than optimal. Therefore, it is necessary to apply the Contextual Teaching and Learning learning model to improve student learning outcomes. The formulation of the problem in this study is whether the application of the Contextual Teaching and Learning learning model can improve student learning outcomes for class VIII FIQIH subjects at MTs Teladan Gebang. The goal to be achieved in this study is to determine the effect of the Contextual Teaching and Learning learning model on student learning outcomes. Class VIII Fiqh subjects at MTs Teladan Gebang. The type of research used is classroom action research with the design used is pretest and posttest. This research was conducted in class VIII MTs Teladan Gebang. Data collection techniques used observations, tests and interviews, then analyzed using hypothesis testing. The results showed that the average score obtained by class VIII at MTs Teladan Gebang in the Pre Test was 58 with 7 students' completeness (21.87). %). In Cycle I, the average student score was 71.34 with a completeness of 20 students (62.5%). In Cycle II the average score of students is 85 with student completeness as many as 32 people (87.5%). This proves that there is a significant effect of the Contextual Teaching and Learning learning model on student learning outcomes for Fiqh Class VIII MTs Teladan Gebang..